E-technologies : embracing the Internet of Things : 7th International Conference, MCETECH 2017, Ottawa, ON, Canada, May 17-19, 2017, Proceedings /: embracing the Internet of Things : 7th International Conference, MCETECH 2017, Ottawa, ON, Canada, May 17-19, 2017, Proceedings. (2017) - Unknown
No abstract available